Consumption patterns of processed foods of Filipino urban middle-income families - Estrellado, Leilani G. (1997)
A survey was conducted among urban middle-income families to determine their awareness, attitudes, and behaviors towards processed foods. A total of 162 out of the 615 respondents participated in the survey. Responses from 17 participants were not included because of incomplete entries. Results showed that 99% were aware that canned foods, dried foods, tocino, ham, cheese, noodles, etc. are processed foods; 88.28% had knowledge about processed foods and were able to describe them. All the families eat processed foods because it is convenient to prepare, easy to buy, cheap, delicious and nutritious. Consumers were likewise influenced by friend and advertisements and have the tendency to follow the latest trend. The most commonly consumed processed food was instant noodles (91.03%). The consumption pattern of the middle-income group reflected their personal and economic backgrounds.